2010
DOI: 10.1182/blood-2009-12-261586
|View full text |Cite
|
Sign up to set email alerts
|

First report of phase 2 study of dasatinib with hyper-CVAD for the frontline treatment of patients with Philadelphia chromosome–positive (Ph+) acute lymphoblastic leukemia

Abstract: The combination of cytotoxic chemotherapy and imatinib has improved the outcome for patients with Philadelphia chromosome-positive (Ph ؉ ) acute lymphoblastic leukemia (ALL). Dasatinib has significant clinical activity in patients with imatinib resistance. We examined the efficacy and safety of combining chemotherapy with dasatinib for patients with Ph ؉ ALL. Newly diagnosed patients received dasatinib 50 mg by mouth twice per day (or 100 mg daily) for the first 14 days of each of 8 cycles of alternating hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
247
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 307 publications
(265 citation statements)
references
References 40 publications
10
247
1
7
Order By: Relevance
“…We continue, therefore, to support a strategy that allows a CHR to be obtained in virtually all patients, including the elderly, based on this chemotherapy-free approach. Furthermore, our study confirms the importance of MRD, the negativity of which should be a major objective in this disease: a higher rate of MRD negativity is likely to be achieved with the inclusion of 2 nd -and, more likely, 3 rd -generation TKI such as ponatinib, which have been proven to have a greater debulking effect, 9,14,16,55 and might possibly be more active in patients with the BCR-ABL p210 form, given the lower MRD clearance observed in this subgroup of patients. As far as ponatinib is concerned, a recent study from the MDACC 55 on 37 patients has indeed shown that its use as upfront therapy, combined with chemotherapy, is able to induce extremely promising results with 2-year event-free survival (EFS) and OS of 81% and 80%, respectively, although 6 toxic deaths were recorded.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…We continue, therefore, to support a strategy that allows a CHR to be obtained in virtually all patients, including the elderly, based on this chemotherapy-free approach. Furthermore, our study confirms the importance of MRD, the negativity of which should be a major objective in this disease: a higher rate of MRD negativity is likely to be achieved with the inclusion of 2 nd -and, more likely, 3 rd -generation TKI such as ponatinib, which have been proven to have a greater debulking effect, 9,14,16,55 and might possibly be more active in patients with the BCR-ABL p210 form, given the lower MRD clearance observed in this subgroup of patients. As far as ponatinib is concerned, a recent study from the MDACC 55 on 37 patients has indeed shown that its use as upfront therapy, combined with chemotherapy, is able to induce extremely promising results with 2-year event-free survival (EFS) and OS of 81% and 80%, respectively, although 6 toxic deaths were recorded.…”
supporting
confidence: 75%
“…5,6,10,12,13,15,[18][19][20][21]34,35 Furthermore, our schedule has the advantage that there are fewer deaths during induction treatment, in contrast to the majority of the combination studies in which, with few exceptions, 5 toxic deaths were recorded in 2%-7% of cases. 6,8,[12][13][14][18][19][20] Indeed, toxicity was recorded in the initial combination protocol (imatinib+chemotherapy) that led to the final amendment to a sequential strategy. These results indicate that the induction treatment for adult Ph + ALL can be effectively based on the administration of imatinib plus steroids, without systemic chemotherapy, which enables a CHR to be obtained in virtually all patients with no deaths in induction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Response rates with combinations of TKIs and chemotherapy are 40% in nonlymphoid BP CML and 70-80% in lymphoid BP CML [81][82][83]. Median survival times are 6-12 months, and 12-24 months, respectively.…”
Section: Advanced Stage CMLmentioning
confidence: 99%